Freshmen's Difficulties with IELTS Writing Task 2 - Phuong, Bui Thi Kim; Hien, Vuong Thuy (VNU Journal of Science: Education Research; Vol 41 No 4DO - 10.25073/2588-1159/vnuer.5268, 2025)
IELTS Writing Task 2 is crucial for assessing students' academic writing skills, focusing on their ability to construct and communicate arguments. The study was conducted to examine the difficulties faced by first-year engineering students in Vietnam in writing IELTS Task 2, based on four criteria: Task Response, Coherence & Cohesion, Lexical Resource, and Grammatical Range & Accuracy. An online survey of 120 students revealed significant struggles with Lexical Resource and Coherence & Cohesion, with Lexical Resource being the most challenging. Students often rely on common vocabulary and incorrect word forms. For Coherence & Cohesion, the incorrect use and underuse of linking words are major issues. While Task Response and Grammatical Range & Accuracy are less problematic, students still face challenges with background knowledge, idea development, sentence structure, articles, and word order. Higher TOEIC scores correlate with fewer difficulties in Task 2, suggesting a link between language proficiency and writing performance. The study is believed to contribute to a clearer understanding of the specific difficulties that Vietnamese EFL learners face when writing IELTS Task 2  and enable IELTS instructors at the university to adapt their teaching methods to better support students in overcoming these challenges.